2014
DOI: 10.9790/0853-13433943
|View full text |Cite
|
Sign up to set email alerts
|

Role of Platelet count as important prognostic marker in Pregnancy Induced Hypertension

Abstract: : Introduction: Pregnancy induced hypertension (PIH) includes gestational hypertension

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…18 Similarly Sameer et al observed patients of mild pre eclampsia and severe pre-eclampsia were all more frequent in primiparous women accounting for 66.03% and 65.51% cases respectively. 19 In present study severe pre-eclampsia 67.5% patients were primigravidae, followed by 22.5% cases of second gravidae and 10% of third or more gravidae. The present findings correlate with authors in respect of severe preeclampsia.…”
Section: Discussionsupporting
confidence: 48%
“…18 Similarly Sameer et al observed patients of mild pre eclampsia and severe pre-eclampsia were all more frequent in primiparous women accounting for 66.03% and 65.51% cases respectively. 19 In present study severe pre-eclampsia 67.5% patients were primigravidae, followed by 22.5% cases of second gravidae and 10% of third or more gravidae. The present findings correlate with authors in respect of severe preeclampsia.…”
Section: Discussionsupporting
confidence: 48%
“…Similarly, another study [ 29 ] reported a similar finding of 30 cases of thrombocytopenia; among these, 9 cases were in non-severe pre-eclampsia and 21 in severe pre-eclampsia. On the contrary, other studies [ 39 , 40 ] showed a slightly higher number of cases, 33 cases (56%) within the severe pre-eclampsia group. Other studies [ 41 , 42 ] found 11 and 16 cases of severe pre-eclampsia, respectively.…”
Section: Discussionmentioning
confidence: 65%
“…Thrombocytopenia in pregnancy-induced hypertensive women may be due to increased adherence of platelets at the site of damaged vascular endothelium leading to increased consumption and secondary destruction of platelets. There is activation of platelets along with increased degranulation leading to decrease in platelet life span and increase in number of immature platelets in peripheral blood smears [1,4].…”
Section: Introductionmentioning
confidence: 99%